2020
DOI: 10.13111/2066-8201.2020.12.3.13
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the obstacle on the hydraulic response of the composite hydraulic structure

Abstract: Experimental investigations are carried out to study the physics of the flow that passes weir-gate hydraulic structure and encounters obstruction with or without installation of downstream opening. This study approaches the comparison between two different options; the first option deals with free flow condition while the second option deals with submerged flow condition. Various cases are performed considering different hydraulics variables and dimensions variables to evaluate the existence of obstruction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Table (1) shows the selected dimension of weirgate structure. Figure (1) illustrates the shapes of weir-gate structure and figure (2) illustrates the entire hydraulic system which includes both the weir-gate structure and blocks.…”
Section: Table (1): the Model Dimensions And Details Of Different Shapes Of Weir And Ellipse Gatementioning
confidence: 99%
See 2 more Smart Citations
“…Table (1) shows the selected dimension of weirgate structure. Figure (1) illustrates the shapes of weir-gate structure and figure (2) illustrates the entire hydraulic system which includes both the weir-gate structure and blocks.…”
Section: Table (1): the Model Dimensions And Details Of Different Shapes Of Weir And Ellipse Gatementioning
confidence: 99%
“…Table (1) shows the selected dimension of weirgate structure. Figure (1) illustrates the shapes of weir-gate structure and figure (2) illustrates the entire hydraulic system which includes both the weir-gate structure and blocks. In each experiment, the following are measured: upstream water depth, water head above weir sharp crest, actual discharge and water depth at flume downstream.…”
Section: Table (1): the Model Dimensions And Details Of Different Shapes Of Weir And Ellipse Gatementioning
confidence: 99%
See 1 more Smart Citation
“…Several hydraulic parameters which dominate the discharge structure are also being studied. [15] tried to carry out many experiments in order to investigate the impact of the submerged obstacles with the opening and without the opening on the hydraulic response of the weir-gate structure. From the results, it is found that the obstacles have a major impact on the flow pattern of the discharge structure.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, various hydraulics variables and dimensions variables are considered in the study. [16] tried to conduct many experiments to reveal the impact of the submerged barriers on the hydraulic response of the combined weir-gate hydraulic structure. From the results, it is found that the barriers have a major influence on the hydraulic variables of the discharge structure.…”
Section: Introductionmentioning
confidence: 99%